Match Running Performance and Exercise Intensity in Elite Female Rugby Sevens - Alcaraz, P. E.; Abraldes, J. A.; Ferragut, C.; Vila, H.; Rodriguez, N.; Argudo, F. M. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to describe the match-play demands of professional female rugby players competing in Rugby Sevens (Rugby 7's) matches. Time-motion analyses (global position system) were performed on 12 elite female rugby players during 5 competitive matches in a 2-day international tournament. Data revealed that players covered an average distance of 1,556.2 ± 189.3 m per game (14 minutes). Over this distance, 29.7% (462.6 ± 94.6 m) was spent standing and walking, 33.2% (515.9 ± 88.6 m) jogging, 11.6% (181.0 ± 61.4 m) cruising, 16.4% (255.7 ± 88.3 m) striding, 3.7% (57.1 ± 40.8 m) high-intensity running, and 5.4% (84.0 ± 64.8 m) sprinting. The average maximal distance of sprints, number of sprints, minimum distance of sprint, and mean sprint distance over the game were as follows: 25.8 ± 16.1 m, 5.3 ± 3.2 sprints, 6.5 ± 2.0 m, and 17.2 ± 8.8 m, respectively. The players' work-to-rest ratio was 1:0.4. For over 75% of the game, the players were exposed to heart rates (HRs) >80% of their maximal HR. There were no statistical differences between the first and second halves in any of the variables analyzed. This study suggests that the physical demands of Rugby 7's are quite different from those reported in other rugby codes. For players and teams to remain competitive in female Rugby Sevens, coaching, conditioning, and physical fitness testing should reflect these current demands.